Anticancer Natural Products: Evolution and their Biosynthetic Site-Selective Conjugation to Antibodies - Vanner, Stephanie (My University, 2014)
Natural products are an important resource for cancer therapy, with highly potent and diverse anticancer activities. Natural product biosynthesis is well comprehended, however the evolutionary principles governing the alteration of enzymatic assembly lines to yield molecules with activity toward distinct various cellular targets are not understood. This gap in knowledge hinders efforts to synthetically combinatorialize assembly lines to yield “unnatural” natural products with important or hybrid activity toward up-regulated targets in cancer. Furthermore, natural products did not evolve in the context of mammalian systems and would benefit from a delivery mechanism to cancerous cells to improve their ability to generate successful clinical outcomes. Consequently, natural products were linked to antibodies targeted to cell surface proteins up-regulated on cancer cells, generating antibody-drug conjugates (ADC). The conjugation methodology is problematic by yielding ADCs with varying numbers of drugs loaded per antibody. This lack of batch-to-batch standardization limits our ability to completely evaluate the safety profiles and efficacy of ADCs and determine proper dosages for patients. In this research, light was shed on biosynthetic evolutionary changes through the study of the antimycin-type family of depsipeptides, specifically demonstrating that modular insertions or deletions lead to natural product structural diversification. Additionally, a novel biosynthetic enzymatic method was established to site-selectively conjugate natural products to antibodies in order to facilitate the development of more sophisticated cancer therapies.
Keywords: natural product; antibody-drug conjugate; cancer